Anti-ulcer Activity of Berberine Isolated from Berberis aristata in Wistar Albino Rats - Ashwini S. Gawade; anuja N. Bhalerao; Prachi D. Bhor; Nupur A. Barve; Anshuvar A. Dhainje; Sanika P. Kokate; Snehal A. Mahadar; Dr. Kiran C. Mahajan; Dr. Ganesh Y. Dama (The Bioscan, 2026)
Peptic ulcer disease (PUD) is a multifactorial gastrointestinal disorder associated with excessive gastric acid secretion, oxidative stress, Helicobacter pylori infection, alcohol consumption, and prolonged use of non-steroidal anti-inflammatory drugs. Herbal compounds possessing antioxidant and cytoprotective properties have gained attention as safer alternatives for ulcer management. The present study investigated the anti-ulcer activity of berberine isolated from Berberis aristata using an ethanol-induced gastric ulcer model in Wistar albino rats. Acute oral toxicity studies were conducted according to OECD guideline 425, and berberine was found to be safe at the selected dose range. Animals were divided into five groups consisting of normal control, ethanol control, standard treatment with omeprazole (20 mg/kg), berberine low dose (50 mg/kg), and berberine high dose (100 mg/kg). Gastric parameters including ulcer index, percentage ulcer inhibition, gastric volume, gastric pH, and total acidity were evaluated. Histopathological examination of gastric tissues was also performed. Berberine treatment significantly reduced ulcer index and gastric acidity while improving gastric pH and mucosal integrity compared with the ethanol control group. The high-dose berberine group showed gastroprotective activity comparable to omeprazole. Histopathological findings further confirmed reduced mucosal erosion and inflammation in berberine-treated animals. The study demonstrates that berberine possesses significant anti-ulcer activity, possibly mediated through antioxidant and cytoprotective mechanisms.